A combination of borage seed oil and quercetin reduces fat accumulation and improves insulin sensitivity in obese rats. Issue 5 (11th May 2020) - Aranaz, Paula; Zabala, María; Romo-Hualde, Ana; Navarro-Herrera, David; López-Yoldi, Miguel; Vizmanos, José Luis; Martínez, J. Alfredo; Milagro, Fermín I.; González-Navarro, Carlos J.
Abstract : Borage seed oil (BSO) combined with quercetin improves glucose tolerance, insulin sensitivity, liver steatosis and adiposity in pre-obese rats. The combination also inhibits adipogenesis in vitro by affecting some adipogenesis-key factors. Abstract : The metabolic properties of omega-6 fatty acid consumption are being increasingly accepted. We had previously observed that supplementation with a borage seed oil (BSO), as a source of linoleic (18:2n-6; LA) and gamma-linolenic (18:3n-6; GLA) acids, reduces body weight and visceral adiposity and improves insulin sensitivity in a diet-induced obesity model of Wistar rats. Here, it was investigated whether the anti-obesogenic properties of BSO could be maintained in a pre-obese model of rats, and if these effects are enhanced by a combination with low doses of quercetin, together with its potential role in the regulation of the adipocyte biology. The combination of BSO and quercetin during 8 weeks was able to ameliorate glucose intolerance and insulin resistance, and to improve liver steatosis. Although no effects were observed on body weight, animals supplemented with this combination exhibited a lower proportion of visceral adiposity. In addition, in vitro differentiation of epididymal adipose-precursor cells of the BSO-treated animals exhibited a down-regulation of Fasn, Glut4, Pparg and Srebp1 genes, in comparison with the control group. Finally, in vitro evaluation of the components of BSO demonstrated that the anti-adipogenic activity of quercetin was significantly potentiated by the combination with both LA and GLA through the down-regulation of different adipogenesis-key genes in 3T3-L1 cells. All these data suggest that omega-6 fatty acids LA and GLA, and their natural sources such as BSO, could be combined with quercetin to potentiate their effects in the prevention of the excess of adiposity and the insulin resistance.